Desain Sistem Pemadam Kebakaran Jalur Hydrant pada Galangan di Kalimantan - Annas Firmansyah; Projek Priyonggo Sumangun; Lely Pramesti (Proceedings Conference on Marine Engineering and its Application, 2023)
Shipyards have facilities that have the potential to cause fires because there is work that generatesheat and contains flammable materials. The existing hydrant system at the shipyard is still simple and does notcover the entire area. Therefore, it is necessary to plan a hydrant system that can cover all areas in accordancewith NFPA and SNI standards. Planning begins with determining the number and placement of hydrant pillars,pipe routing, head loss calculations, and pump selection. The pipeline requires 7.776 m of 8-inch pipe, and 6-inch pipe requires 1915.477 m of pipe. The total head losses obtained from the calculation at the farthesthydrant pillar is 217.426 m. The selected pump is a Wilo 150 GF with a pump head of 240 m and a capacity of1250 US GPM.